Pengaruh Sikap, Norma Subjektif, Persepsi Kontrol Perilaku dan Muslim’s View of Allah terhadap Keputusan Whistleblowing - Desmita, Desmita; Helmayunita, Nayang (Jurnal Nuansa Karya Akuntansi, 2023)
This study aims to determine the extent the influence of attitudes, subjective norms, perceived behavioral control and muslims' view of Allah on whistleblowing decisions. This research is quantitative research. The sample selection in this study uses a purposive sampling method in which the respondents are the government employees in Regional Revenue Agency of West Sumatra Province. Data collection techniques used in this study were using a questionnaire. This study succeeded in finding the results that attitudes, subjective norms and Muslim's view of Allah have an effect on whistleblowing decisions. While the behavioral control perception variable has no effect on whistleblowing decisions.